Protest in fiction : an approach to Alex la Guma - Cornwell, David Gareth Napier (Rhodes University, Faculty of Humanities, Department of Literary Studies in English, 1979)
From Introduction: Thus for the black South African, the act of creative writing is inescapably a form of political action, and unless he turns his back on the reality which confronts him and retreats into a private imaginary world, it is also a form of social action, Yet Ezekiel Mphahlele has rightly cautioned that "creating an imaginary world" can never be an effective substitute for social act ion . Composing fictions about social and political problems is an indubitably oblique way of seeking a solution to them, and even the tendentious recreation of reality is only a metaphor for its actual transformation. Protest writing in South Africa is paradoxically a form of social action which is also only a parasitical imitation of social action, and therefore its avoidance . The freedom of literary creation described above is ambiguously not only a freedom to express reality, but also a freedom from the constraints of reality. And this suggests why the outlaw was such an important symbol to an earlier generation of rather more self-conscious writers.
Keywords: La Guma, Alex; South African literature (English) -- Black authors -- History and criticism; Protest literature, -- South African (English) -- History and criticism